Phantom development for daily checks in electron intraoperative radiotherapy with a mobile linac. (August 2020) - Pérez-Calatayud, José; Sanchis-Sánchez, Enrique; Collado, Javier; González, Vicente; Pérez-Calatayud, I.; Pérez-Calatayud, M.J.; Chimeno, José; Carmona, Vicente; Luis Bonet-Sancho, José; García-Sánchez, Antonio J.; Sanchis, Enrique
Highlights: Development of a phantom and application for daily test in a mobile intraoperative linac. Efficient setup and a complete dosimetric information. Use of ionization chambers with minimum saturation effect. Abstract: Purpose: IORT with mobile linear accelerators is a well-established modality where the dose rate and, therefore, the dose per pulse are very high. The constancy of the dosimetric parameters of the accelerator has to be checked daily. The aim of this work is to develop a phantom with embedded detectors to improve both accuracy and efficiency in the daily test of an IORT linac at the surgery room. Methods: The developed phantom is manufactured with transparent polymethyl methacrylate (PMMA), allocating 6 parallel-plate chambers: a central one to evaluate the on-axis beam output, another on-axis one placed at a fixed depth under the previous one to evaluate the energy constancy and four off-axis chambers to evaluate the flatness and symmetry. To analyse the readings a specific application has been developed. Results: For all chambers and energies, the mean saturation and polarization corrections were smaller than 0.7%. The beam is monitored at different levels of the clinical beam. Output, energy constancy and flatness correlate very well with the correspondent values with the complete applicator. During the first six months of clinical use the beam dosimetric parameters showed excellent stability. Conclusions: A phantom has been developed with embedded parallel plate chambers attached to the upper applicator part of an IORT linac. The phantom allows a very efficient setup reducing the time to check the parameters. It provides complete dosimetric information (output, energy and flatness) with just one shot and using ionization chambers with minimum saturation effect, as this highly pulsed beam requires.